Biomaterials in Valvular Heart Diseases - Taghizadeh, Bita; Ghavami, Laleh; Derakhshankhah, Hossein; Zangene, Ehsan; Razmi, Mahdieh; Jaymand, Mehdi; Zarrintaj, Payam; Zarghami, Nosratollah; Jaafari, Mahmoud Reza; Moallem Shahri, Matin; Moghaddasian, Adrineh; Tayebi, Lobat; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases (CVD) including valvular disease, coronary heart disease, aortic disease, myocardial infarction, cardiac myopathy, heart failure etc., are considered the leading cause of death worldwide. The global commitment to reduce mortality rates related to CVD has enhanced the need for new therapeutic approaches. During the past decade, development of innovative pharmacological and surgical approaches has dramatically improved the quality of life for CVD patients, yet the search for low cost, more effective and less invasive approaches is ongoing. The gold standard approach for CVD management is to replace or repair injured cardiac tissue with natural or synthetic biomaterials. Application of these biomaterials for cardiac regeneration and repair holds a great promise for use in CVD treatment. The focus of the present review is the current use of different types of biomaterials in treatment of valvular heart diseases.